THE EFFECT OF CRICKET (Gryllus mitratus Burm) FLOUR SUBSTITUTION IN COMMERCIAL RATIO ON THE ORGANOLEPTIC QUALITY OF BROILER MEAT - E. B., SURBAKTI; ASTAWA, I P. A.; LINDAWATI, S. A. (Majalah Ilmiah Peternakan; Vol 28 No 1 (2025): Vol. 28 No. 1 (2025), 2025)
This research aims to determine the effect of substitution of cricket flour (Gryllus mitratus Burm) in commer- cial rations on the organoleptic quality of broiler meat. This research was carried out at the Sesetan Laboratory, Faculty of Animal Husbandry, Udayana University, which lasted for 35 days. The design used in this research was a Completely Randomized Design (CRD) with 4 treatments and 4 replications, each replication consisting of four broilers. The four treatments are: P0 (Giving commercial rations without substitution), P1 (Giving commercial rati- ons substituted with 2% cricket flour), P2 (Giving commercial rations substituted with 4% cricket flour), P3 (Giving commercial rations substituted with 6% cricket flour). The variable observed was the organoleptic quality of Broiler meat using hedonic liking and hedonic quality tests. The results showed that the substitution of cricket flour (Gryl- lus mitratus Burm) 2%, 4%, 6% in commercial rations on the organoleptic quality of broiler meat was significantly different. From the research results it can be concluded that the substitution of 6% cricket (Gryllus mitratus Burm) flour in commercial rations obtained the highest score of favorability on the organoleptic quality of broiler meat.